2012
DOI: 10.1253/circj.cj-12-1306
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Ventricular Fibrillation, Early Repolarization and Other J Wave-Related Ventricular Fibrillation Syndromes

Abstract: Current clinical and experimental data demonstrate that the electrocardiographic J wave plays a critical role in the pathogenesis of ventricular fibrillation (VF) in patients with Brugada syndrome (BS) and early repolarization (ER) syndrome (ERS). This has generated renewed interest in the presence of J waves and ERS in the general population, yet the identification of high-risk ECG markers and the risk stratification of subjects with ERS remain to be established. More recently, this concept has been expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…Rolf et al 9 reported a patient with BS with a resting ECG intermittently displaying a saddleback type and coved type ECG pattern, which was masked when CRBBB occurred. A similar case of a BS patient was reported by Nam 24 in 2012. On some occasions, we might be able to unmask BS in patients with CRBBB.…”
Section: Proof Of Coexisting Bs With Crbbbsupporting
confidence: 78%
“…Rolf et al 9 reported a patient with BS with a resting ECG intermittently displaying a saddleback type and coved type ECG pattern, which was masked when CRBBB occurred. A similar case of a BS patient was reported by Nam 24 in 2012. On some occasions, we might be able to unmask BS in patients with CRBBB.…”
Section: Proof Of Coexisting Bs With Crbbbsupporting
confidence: 78%
“…This difference in action potential activity leads to the development of a transmural voltage gradient that manifests as a prominent J wave on ECG. 15 This mechanism can lead to phase 2 reentry. Severe hypothermia may increase the transmural voltage gradient, resulting in a higher amplitude of J waves in more areas.…”
Section: Discussionmentioning
confidence: 99%
“…This ECG sign is, however, not pathognomonic of hypothermia and also occurs in many other conditions, such as hypercalcemia [22], certain central nervous system lesions (subarachnoidal hemorrhage or cerebral injuries), Brugada syndrome, as well as in healthy persons with early repolarization [6][7][8]. Multiple medications, including class Ia and Ic anti-arrhythmic agents, cocaine, psychotropic medications, lithium, and antihistamines, can also simulate or provoke Brugada-or early repolarization-ECG patterns [1].…”
Section: Discussionmentioning
confidence: 99%
“…J-waves originate from the heterogeneous distribution of a transient outward current-mediated spike-and-dome morphology of the action potential across the ventricular wall. The presence of a prominent action potential notch in the epicardium, but not the endocardium, provides a voltage gradient that manifests as a J-wave or elevated J-point in the electrocardiogram [7,8]. Under hypothermic conditions, the epicardial potassium current is increased relative to the current in the endocardium during ventricular repolarization [8], producing a transmural voltage gradient that is reflected on the surface electrocardiogram as prominent J-waves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation